Dendritic polyglycerolamine as a functional antifouling coating of gold surfaces - Paez, Julieta Irene (2012)
Dendritic polyglycerol (PG) functionalized surfaces represent a good alternative for preparation of protein resistant materials, whose versatility can be enhanced by conferring them the ability to bind particular biomolecules of interest to the surface. In this work, PG derivatives bearing disulfide and different loadings of amino moieties (0–14%) were synthesized and attached to gold surfaces. The modified surfaces were characterized by means of infrared reflection adsorption spectroscopy (FT-IRRAS), X-ray photoelectron spectroscopy (XPS), and contact angle measurements. The protein resistance properties of the PG-modified surfaces were evaluated by surface plasmon resonance (SPR) spectroscopy using fibrinogen, albumin, pepsin, and lysozyme as model proteins. The availability and accessibility of the amino groups to bind biomolecules were assessed by fluorescence measurements. This study demonstrates that PG-coated surfaces with amino contents up to 9% still show very good protein resistant properties. At the same time, the amino moieties on the surface are available and reactive for selective ligand attachment. By fluorescence labeled DNA hybridization, the high selectivity of these functional surfaces could be demonstrated.